2017
DOI: 10.1080/03007995.2017.1318121
|View full text |Cite
|
Sign up to set email alerts
|

Persistence with rapid-acting insulin and its association with A1C level and severe hypoglycemia among elderly patients with type 2 diabetes

Abstract: Objective To examine the persistence with rapid-acting insulin (RAI) and its association with clinical outcomes among elderly patients with type 2 diabetes (T2D). Methods This observational, retrospective cohort study analyzed RAI persistence and its association with change in A1C and risk of severe hypoglycemia among elderly (≥65 years) Medicare beneficiaries with T2D who added RAI to their basal insulin regimen. Results Among T2D patients with >1 RAI prescriptions (n=3,927), only 21% were persistent. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In total, there were 17 studies based on commercial administrative/claims data [ 5 , 7 , 8 , 14 , 15 , 19 , 25 35 ], 1 based on US veterans’ data (linked claims and medical records) [ 11 ], 12 studies based on medical records [ 10 , 12 , 16 , 17 , 20 24 , 36 38 ] (6 of these also used surveys [ 10 , 12 , 21 24 ] and 1 used Geisinger electronic medical records [ 17 ]), 2 based on national surveys [ 9 , 13 ], 1 based on a physician survey [ 6 ], and 1 based on a diabetic registry with survey [ 18 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, there were 17 studies based on commercial administrative/claims data [ 5 , 7 , 8 , 14 , 15 , 19 , 25 35 ], 1 based on US veterans’ data (linked claims and medical records) [ 11 ], 12 studies based on medical records [ 10 , 12 , 16 , 17 , 20 24 , 36 38 ] (6 of these also used surveys [ 10 , 12 , 21 24 ] and 1 used Geisinger electronic medical records [ 17 ]), 2 based on national surveys [ 9 , 13 ], 1 based on a physician survey [ 6 ], and 1 based on a diabetic registry with survey [ 18 ]…”
Section: Resultsmentioning
confidence: 99%
“…A total of 18 published articles (including Levin et al [ 32 ]) reported relationships between insulin adherence or persistence and HbA1c. Of these 18, 5 studies [ 5 , 17 , 19 , 21 , 32 ] examined persistence and 13 examined adherence. Here too, study designs varied widely, precluding any evaluation of trends or synthesis of study results.…”
Section: Glycemic Control Resultsmentioning
confidence: 99%
“…Earlier studies examining persistence with a single insulin type have reported widely variable results ranging from 29% to 69% persistence with basal insulin at 1 year after initiation 16,[25][26][27] and from 18% to 34% persistence with rapid-acting or prandial insulin at 1 year after initiation. 17,18,28 Possible reasons for the wide variation include different study populations (e.g., elderly vs. all adults) and the different measures of persistence used to address the challenge of determining persistence with an injectable agent such as insulin via prescription or claims records. 2,14,19 As described in 2 systematic reviews, reported measures of persistence have included mean times to nonpersistence, defined using varying times without a gap between prescription refills (usually 60 or 90 days), a prespecified number of refills within a prespecified time period, the percentages of patients without a treatment gap, and the hazard or odds of nonpersistence.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…However, the adherence and persistence rates of insulin treatment are generally suboptimal. For example, one-year persistence rates of insulin treatment, measured as the percentage of patients who remained on therapy, were only 20–66.8% [ 62 , 63 ]. Similarly, adherence to insulin was low; 58.5% of T2DM patients on insulin therapy scored poor adherence (scoring below 6) on the Morisky-Green Questionnaire [ 64 ].…”
Section: Insulinmentioning
confidence: 99%